Short-Circuit Characteristic Analysis Model and Real-time Risk Assessment of Protection Considering Uncertainties of New Energy Output - LIANG Yuansheng, XU Zheng, LI Haifeng, WANG Gang, CHEN Haoyong, LI Jia (Dianli jianshe)
In the context of flexible DC interconnection and the large-scale integration of new energy， when a system experiences a short-circuit fault， low-voltage ride-through （LVRT） control causes uncertainty in fault characteristics， increasing the risk of incorrect protection action. This study aims to establish an accurate real-time risk assessment model for protection and combine the characteristics of LVRT control to construct a short-circuit analysis calculation model that takes uncertainty into account. Considering the short-term random fluctuations of the new energy output and measurement errors， an uncertainty analysis model for protection actions was constructed based on the stochastic response surface method to evaluate the probability of incorrect protection actions and to propose a risk assessment and warning method for inaccurate protection actions. Finally， a PSCAD simulation model is constructed to verify the accuracy of the short-circuit calculation model considering LVRT control. Based on Monte Carlo sampling， the probability of the adequacy of protection actions based on the random response surface method and its equivalent effect were verified. Through multiple case scenarios， it was demonstrated that the proposed protection risk warning method can calculate the real-time risk of incorrect protection actions， thereby providing a reference for improving protection measures.